Strain of Synechocystis PCC 6803 with Aberrant Assembly of Photosystem II Contains Tandem Duplication of a Large Chromosomal Region - Tichý, Martin; Bečková, Martina; Kopečná, Jana; Noda, Judith; Sobotka, Roman; Komenda, Josef (Frontiers in Plant Science, 2016)
Cyanobacterium Synechocystis PCC 6803 represents a favored model organism for photosynthetic studies. Its easy transformability allowed construction of a vast number of Synechocystis mutants including many photosynthetically incompetent ones. However, it became clear that there is already a spectrum of Synechocystis “wild-type” substrains with apparently different phenotypes. Here, we analyzed organization of photosynthetic membrane complexes in a standard motile Pasteur collection strain termed PCC and two non-motile glucose-tolerant substrains (named here GT-P and GT-W) previously used as genetic backgrounds for construction of many photosynthetic site directed mutants. Although, both the GT-P and GT-W strains were derived from the same strain constructed and described by Williams in 1988, only GT-P was similar in pigmentation and in the compositions of Photosystem II (PSII) and Photosystem I (PSI) complexes to PCC. In contrast, GT-W contained much more carotenoids but significantly less chlorophyll (Chl), which was reflected by lower level of dimeric PSII and especially trimeric PSI. We found that GT-W was deficient in Chl biosynthesis and contained unusually high level of unassembled D1-D2 reaction center, CP47 and especially CP43. Another specific feature of GT-W was a several fold increase in the level of the Ycf39-Hlip complex previously postulated to participate in the recycling of Chl molecules. Genome re-sequencing revealed that the phenotype of GT-W is related to the tandem duplication of a large region of the chromosome that contains 100 genes including ones encoding D1, Psb28, and other PSII-related proteins as well as Mg-protoporphyrin methylester cyclase (Cycl). Interestingly, the duplication was completely eliminated after keeping GT-W cells on agar plates under photoautotrophic conditions for several months. The GT-W strain without a duplication showed no obvious defects in PSII assembly and resembled the GT-P substrain. Although, we do not exactly know how the duplication affected the GT-W phenotype, we hypothesize that changed stoichiometry of protein components of PSII and Chl biosynthetic machinery encoded by the duplicated region impaired proper assembly and functioning of these multi-subunit complexes. The study also emphasizes the crucial importance of a proper control strain for evaluating Synechocystis mutants.